The gender typing of sports among multiethnic urban secondary school students in Klang Valley Malaysia / Chithra Latha Ramalingam - Chithra Latha, Ramalingam (2016)
In this thesis, I will investigate girls’ and boys’ sports participation in Malaysia. The areas are gender typing in sports participation, the relationship between gender and stereotypes, perceptions and influences and the relationship between gender within ethnicities in relation to stereotyping, perception and influences. This thesis demonstrates the importance of gender by itself and in conjunction with ethnicities in understanding sports participation. The purpose of this thesis is to test the theory of equality that relates to gender and ethnicity (these variables will be the independent variable in this research) to gender typing of sports and its relationship to stereotyping, perception and influences (the dependant variable) for boys and girls at urban schools in the Klang Valley. Independent variable is the variable that influences the values of the dependant variable and the dependant variable is the variable where the values are foretold by the independent variable (Collis & Hussey, 2009).